WW, PH and C-Terminal Domains Cooperate to Direct the Subcellular Localizations of PLEKHA5, PLEKHA6 and PLEKHA7 - Sluysmans, Sophie; Méan, Isabelle; Jond, Lionel; Citi, Sandra (Frontiers in Cell and Developmental Biology, 2021)
PLEKHA5, PLEKHA6, and PLEKHA7 (WW-PLEKHAs) are members of the PLEKHA family of proteins that interact with PDZD11 through their tandem WW domains. WW-PLEKHAs contribute to the trafficking and retention of transmembrane proteins, including nectins, Tspan33, and the copper pump ATP7A, at cell-cell junctions and lateral membranes. However, the structural basis for the distinct subcellular localizations of PLEKHA5, PLEKHA6, and PLEKHA7 is not clear. Here we expressed mutant and chimeric proteins of WW-PLEKHAs in cultured cells to clarify the role of their structural domains in their localization. We found that the WW-mediated interaction between PLEKHA5 and PDZD11 is required for their respective association with cytoplasmic microtubules. The PH domain of PLEKHA5 is required for its localization along the lateral plasma membrane and promotes the lateral localization of PLEKHA7 in a chimeric molecule. Although the PH domain of PLEKHA7 is not required for its localization at the adherens junctions (AJ), it promotes a AJ localization of chimeric proteins. The C-terminal region of PLEKHA6 and PLEKHA7 and the coiled-coil region of PLEKHA7 promote their localization at AJ of epithelial cells. These observations indicate that the localizations of WW-PLEKHAs at specific subcellular sites, where they recruit PDZD11, are the result of multiple cooperative protein-lipid and protein-protein interactions and provide a rational basis for the identification of additional proteins involved in trafficking and sorting of WW-PLEKHAs.